Persons, Situations, Interactions: The History of a Controversy and a Discussion of Theoretical Models - Pervin, Lawrence A. (Academy of Management Review, 1989)
The history of the person-situation controversy is reviewed. Although this controversy is not new, and most psychologists now see themselves as interactionists, they disagree about the kinds of person, situation, and interaction process units that should be emphasized. Two models, a social intelligence model and a goals model, for analyzing person-situation interaction and the question of person-environment congruence are considered.